Composition, characteristics and health promising prospects of black wheat: A review. (June 2021) - Dhua, Subhamoy; Kumar, Kshitiz; Kumar, Yogesh; Singh, Lochan; Sharanagat, Vijay Singh
Abstract: Background: Black wheat is a variety of pigmented wheat developed by crossing purple and blue wheat. The anthocyanin present in the outer layer is responsible for the black color of wheat grain. It consists of numerous nutritional and bioactive compounds including phenolic compounds, anthocyanins, carotenoids, phytic acid essential amino acids, dietary fibers, vitamins and minerals. Scope and research: This review summarizes the chemical composition, bioactive compounds, functional properties and health benefits of black wheat to highlight its potential for different functional food development. Key findings and conclusions: Black wheat (BW) possess higher protein content, dietary fiber, calcium, Vitamin K, total flavonoid (TFC) and phenolic content (TPC), and antioxidant activity than the conventional yellow wheat. The TPC of BW is six times higher than yellow wheat with most abundant phenolic acid being ferulic acid. Around 225 metabolites mainly belonging to flavonoids group differs between black and yellow wheat and are responsible for their colour difference. The expression of structural genes namely TaCHI, TaDFR, TaF3H, TaUGT, TaANS and TaMT was highest in BW than other pigmented and conventional wheat varieties. Consumption of whole BW led to prevention of cardiovascular disease, inflammation, cancer, diabetes, obesity, aging and large bowel protection. Clinical trials have revealed that enhancement of interleukin (IL)-6 induced due to type 2 and tumor necrosis factor (TNF)-α diabetes mellitus was prevented by the BW diet. Nutrient and bioactive compound rich BW offers a great potential to develop healthy functional food. Graphical abstract: Image 1 Highlights: Black wheat is richer in all nutrients compared to yellow wheat. Bioactive compounds are more in black wheat than yellow wheat. Consumption of black wheat reduces various diseases in humans. Gluten strength is sufficient for development of bakery products. Extensive research on different aspects of black wheat is required.